Gestoorde vorsten - Allegaert, Patrick, 1954-; Cailliau, Annemie, 1957-; Couckhuyt, Alexander (Gent : Museum Dr. Guislain, 1999)
Tentoonstelling in het kader van het Keizer Karel herdenkingsjaar 1500-2000
Tekst in het Nederlands, Frans en Engels
Keywords: Exhibitions